Implementación de una red de sensores inalámbricos (WSN) para el condominio Annabella - Saavedra Cano, Carlos Andrés (2015)
A wireless sensors network is an infrastructure to dedicate the monitoring, computing and data communication that to allow an entity administration to implement, monitor and react to events or specific phenomena in a specific environment. The objective of this research is to implement a wireless sensor network, using the protocol ZigBee a the standard IEEE802.15.4, that allow to defending the residents of the “Annabelle” condominium, located in the area of the Inca road Samuel Fritz and Joaquin Sumaita of Quito city, Ecuador. In developing the feasibility of this study, it was established that this provides to the residents of the “Annabella” Condominium security both goods and their members and the technology used ensures the detection of possible threats posed throughout history Condominium….